Inflation at the household level - Greg Kaplan; Sam Schulhofer-Wohl (Federal Reserve Bank of Chicago, 2017)
We use scanner data to estimate inflation rates at the household level. Households' inflation rates have an annual interquartile range of 6.2 to 9.0 percentage points. Most of the heterogeneity comes not from variation in broadly defined consumption bundles but from variation in prices paid for the same types of goods. Lower-income households experience higher inflation, but most cross-sectional variation is uncorrelated with observables. Households' deviations from aggregate inflation exhibit only slightly negative serial correlation. Almost all variability in a household's inflation rate comes from variability in household-level prices relative to average prices, not from variability in aggregate inflation.
Keywords: D12; D30; E31; 330; Inflation; Heterogeneity